2011
DOI: 10.14710/jitaa.36.1.14-20
|View full text |Cite
|
Sign up to set email alerts
|

PREDICTION MODELS FOR OLFACTORY METABOLIC AND SOWS %RNAreticulocyt (RNArt) BY MEASUREMENT OF ATMOSPHERIC AMMONIA EXPOSURE AND MICROCLIMATE LEVEL

Abstract: Twenty sows housed indoors in individual stalls were used to determine the relationships between atmospheric ammonia exposure and microclimate on olfactory metabolic and sows RNAreticulocyt, and to know the prediction models of the olfactory metabolic and sows RNAreticulocyt by measurement of atmospheric ammonia exposure and microclimate level. Result indicated a significantly negative effect of ammonia on commonly olfactory metabolic parameters and %RNA reticulocyt . The results also showed that ammonia has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Mushawwir et al (2018) have shown the effect of some natural extracts to an increase in oxygen consumption as an effect of increasing levels of transferrin in poultry. Zahner et al (2014) also reported improvements in metabolic rate and the other investigator showed an increase level of antioxidants in small ruminants, and in beef cattle (Mushawwir et al 2010(Mushawwir et al ,2011Roland et al 2016), and dairy cows and rats (Arya et al 2014;Monteiro et al 2016;Nguyen et al 2016). The results of research by Hidayat et al (2011) showed that feeding natural extracts increased the digestibility and absorption of nutrients in the rumen.…”
Section: Antioxidants Statusmentioning
confidence: 97%
See 1 more Smart Citation
“…Mushawwir et al (2018) have shown the effect of some natural extracts to an increase in oxygen consumption as an effect of increasing levels of transferrin in poultry. Zahner et al (2014) also reported improvements in metabolic rate and the other investigator showed an increase level of antioxidants in small ruminants, and in beef cattle (Mushawwir et al 2010(Mushawwir et al ,2011Roland et al 2016), and dairy cows and rats (Arya et al 2014;Monteiro et al 2016;Nguyen et al 2016). The results of research by Hidayat et al (2011) showed that feeding natural extracts increased the digestibility and absorption of nutrients in the rumen.…”
Section: Antioxidants Statusmentioning
confidence: 97%
“…It is suspected that with an increase in total phenol, antioxidant activity is higher and greater than low phenol levels. Duckweed is often used as a traditional medicine because it has a variety of benefits such as: anticancer, antidiabetic (Korivi et al 2012), antifungal (Vizzotto et al 2015), antimicrobial (Pickler et al 2013;Tian et al 2015), anti-inflammatory and analgesic (Xu et al 2015;Moreno et al 2015;Kusmayadi et al 2018), antioxidant (Mushawwir et al 2010(Mushawwir et al , 2011Hecker and McGarvey 2011;Fabris et al 2017), and sedative activity from the nervous system (Azis et al 2012;De Castro et al 2013;Pouyssegur and Mechta-Grigoriou 2016). These activities can be produced because of the role of chemical compounds contained therein such as alkaloids, phenols, flavonoids (He et al 2009) and the other report showed some chemicals such as tannins, anthocyanins, glycosides, bufadienolides, saponins, coumarin, sitosterol, quinine, and lectins (O'Brien et al 2010;Rhoads et al 2013;Shehab-El-Deen et al 2014).…”
Section: Antioxidants Statusmentioning
confidence: 99%
“…This was shown by the glycogen levels in the livestock sample group, which was significantly (P <0.05) higher than the cattle group without IC treatment, and with IC treatment at 350 and 400 ppm. The results of this study indicate that IC administration reduces the rate of energy supply from alternative pathways, such as glycogenolysis (Mushawwir et al 2010(Mushawwir et al , 2011Slimen et al 2016). Previous research has also shown that natural extracts reduce glycogenolysis in ruminants ( The intermediate metabolites such as glucose 1phosphate, glucose 6-phosphate, and the enzymes involved, including glycogen phosphorylase, phosphoglucomutase, and glucose 6-phosphatase, during glycogenolysis, appeared to be increased in the livestock group not given IC.…”
Section: Glycogenolysis Pathwaymentioning
confidence: 57%
“…From the results of this study, metabolic balance and the achievement of homeostasis with or without IC administration causes no significant difference in glucose levels between treatment groups. Therefore, this shows that glucose is an important buffer for body fluids (Picker et al 2013;Lee et al 2014;Loyau et al 2014), and maintains blood viscosity (Renaudeau et al 2012;Ma et al 2014;Mushawwir et al 2018), as well as the osmotic pressure of dissolving cells (Mushawwir et al 2011;Royer et al 2016;Hernawan et al 2017).…”
Section: Glycogenolysis Pathwaymentioning
confidence: 99%
“…Increasing environmental temperature is an important problem for the development and growth of quail. The environmental temperature above the comfort zone causes the physiological and biochemical processes to be directed more towards homeostasis (Mushawwir et al, 2010(Mushawwir et al, , 2011(Mushawwir et al, , 2020aAmmer et al, 2018). Homeostasis is increased in order to achieve a balanced degree of organ function and metabolic rate in order to regulate body heat (thermoregulation).…”
Section: Introductionmentioning
confidence: 99%